2012
DOI: 10.1210/jc.2011-3340
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Receptor Blockade Inhibits Growth Hormone-Induced Chemoresistance by Restoring Cytotoxic-Induced Apoptosis in Breast Cancer Cells Independently of Estrogen Receptor Expression

Abstract: In human BC cell lines, GH directly promotes resistance to apoptosis induced by chemotherapeutic drugs independently of ER expression by modulating JNK, further broadening the concept that GH excess may hamper cytotoxic BC treatment. These findings support the hypothesis that blocking GH receptor may be viewed as a potential new therapeutic approach to overcome chemoresistance, especially in ER-negative BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…To the present, GH-induced JNK phosphorylation has been demonstrated in macrophages [34], in NIH 3 T3 fibroblasts [33], and also in chinese hamster ovary cells stably transfected with rat GH receptor cDNA [51]. However, GH has been shown to reduce both basal and doxorubicin-stimulated JNK transcriptional activity and phosphorylation in both MDA-MB-231 and MCF7 cells [52], thus demonstrating the complexity of GH-mediated JNK regulation.…”
Section: Discussionmentioning
confidence: 99%
“…To the present, GH-induced JNK phosphorylation has been demonstrated in macrophages [34], in NIH 3 T3 fibroblasts [33], and also in chinese hamster ovary cells stably transfected with rat GH receptor cDNA [51]. However, GH has been shown to reduce both basal and doxorubicin-stimulated JNK transcriptional activity and phosphorylation in both MDA-MB-231 and MCF7 cells [52], thus demonstrating the complexity of GH-mediated JNK regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Zatelli's group also demonstrated a protective effect of GH in inhibiting doxorubicin induced apoptosis in estrogen-receptor negative breast cancer cells, which was significantly abrogated using Pegvisomant (182). In an in vitro study, Lobie and colleagues had identified autocrine GH causing increased resistance of breast cancer cells (MCF7, T47D, and MDA-MB-231) to mitomycin-C (MMC)-induced apoptosis by protecting against DNA-damage(160).…”
Section: Role Of Gh-ghr In Cancer Therapy Resistancementioning
confidence: 99%
“…The NCI-H727 and NCI-H720 cells were treated with 100 nM everolimus or NVP-BEZ235 for 72 h. Vehicle-treated cells served as the controls. At the end of the incubation period, the cells were washed with PBS and incubated with 1 ml of staining solution (5 mg/ml propidium iodide, 10 mg/ml and analyzed using the FloMax Software (Partec), as described previously (Minoia et al 2012).…”
Section: Flow Cytometrymentioning
confidence: 99%